PEMBIAYAAN MULTI JASA PADA KSPPS BMT AN-NAJAH KANTOR CABANG KAJEN PEKALONGAN DAN PEMBIAYAAN ULTRA MIKRO PADA BMT NU SEJAHTERA - Suci Rahmadhania, Laila; Romadhoni, Serli; Wulandari, Niken; Hanifah, Ummu; Waluyo, Waluyo (JISEF : Journal Of International Sharia Economics And Financial, 2025)
This study aims to analyze the concept and implementation of multi-service financing and ultra-micro financing in Islamic financial institutions. Multi-service financing uses the ijarah contract. This allows customers to benefit from a service, while ultra-micro financing is intended for micro-enterprises that have limited ceilings. This journal uses a qualitative method with a literature study approach to understand the theory and related information. The results of the study indicate that multi-service and ultra-micro financing must be in accordance with sharia principles and avoid parties who oppress and are oppressed. Multi-service financing includes various products such as education financing, hajj, and umrah, with a service fee (ujrah) agreed upon in advance. Ultra-micro financing itself is a continuation of the social assistance program distributed through Non-Bank Financial Institutions (LKBB) with the aim of making micro-enterprises independent.